Designing and evaluating resource-oriented interventions to enhance employee well-being and health - Michel, Alexandra; O’Shea, Deirdre; Hoppe, Annekatrin (Journal of occupational and organizational psychology, 2015)
The author discusses the special issue of the "Journal of Occupational and Organizational Psychology" on "Designing and Evaluating Resource-Oriented Interventions to Enhance Employee Well-being and Health."